Recent Developments in the Bioconversion of Lignocelluloses into Ethanol - . KOESNANDAR; IS HELIANTI; NIKNIK NURHAYATI (Microbiology Indonesia, 2008)
Ethanol has been commercially produced using sugars derived from sugarcane and corn. Recently, research has been focused on the development of thermotolerant and ethanol-tolerant yeast or bacteria that are able to produce ethanol efficiently, as well as the development of lignocellulosic materials as the carbon sources of fermentation. Utilization of lignocellulosic materials as fermentation substrate is promising since they are available in large amounts, renewable and relatively cheap. A lignocellulose biomass is a complex mixture of carbohydrate polymers. In order to develop an efficient process, there have been many attempts to obtain more efficient ways in the conversion of lignocelluloses to ethanol, including pretreatment, enzymatic hydrolysis of lignocelluloses and direct co-culture fermentation. This paper describes the production process of ethanol from starch-containing material, recent developments on the enzymatic bioconversion of lignocelluloses into sugars and their subsequent fermentation into ethanol and the possible recombination of microbes for the direct conversion of lignocelluloses into ethanol.